Reducing Atmospheric Emissions from Land Application of Manure - Marinova, Svetla; Kathijotes, Nicholas (My University, 2010)
In view of the extreme climatic changes that are occurring, all gas inputs into the atmosphere should be investigated, especially carbon dioxide, nitrogen and ammonia. When raising animals, and nearby these farms, large amounts of animal liquid wastes are accumulated. These are used for irrigating and fertilizing nearby fields. During surface application, and in the process of bacterial hydrolysis, considerable quantities of nitrogen, after passing through ammonification, and are liberated into the atmosphere as atmospheric nitrogen. The aim of this paper is to evaluate the quantities of nitrogen loss during application of these liquid wastes, as well as the principle parameters which influence these losses. Model plant under natural conditions was used where using an aspirator unit, the quantity of gaseous nitrogen loss was determined. Series of factors were investigated, as state of soil surface, amount of fertilizer, extent of fertilizer dilution with water, air temperature, soil type, etc. These results show that the largest amount of ammonia nitrogen is evolved in the atmosphere, at surface sprinkling of liquid manure on meadows, pasture-grounds and lawn and at a less degree on fallow land. Some recommendations were made for decreasing atmospheric nitrogen losses up to 25% if immediately after sprinkling the fertilizer or manure plow down or cultivation in 8-10-cm depth is carried out. The nitrogen losses are practically insignificant at larger depth.
Keywords: Manure; Nitrogen emissions; Fertilization rates; Climate changes; Manure; Nitrogen emissions; Fertilization rates; Climate changes